Author Topic: TUT 0501 Quiz 3  (Read 365 times)

Ranran Wang

  • Jr. Member
  • **
  • Posts: 9
  • Karma: 0
    • View Profile
TUT 0501 Quiz 3
« on: October 11, 2019, 03:33:38 PM »
Here is my question and solution for the question I met in Quiz 3.

Nan Yang

  • Jr. Member
  • **
  • Posts: 6
  • Karma: 2
    • View Profile
Re: TUT 0501 Quiz 3
« Reply #1 on: October 11, 2019, 04:11:12 PM »
we got the same question and I type the solution of this question.
Question: find the general solution of the given differential equation
y'' $-$ 2y' $-$ 2y = 0


Solution:
Let y'' $-$ 2y' $-$ 2y = 0 be equation (1)
we assume that $y= e^{rt}$ is solution of (1)
Then we have:
  $y= e^{rt}$ 
$y'= re^{rt}$
$y''= r^2e^{rt}$
we substitute them into equation (1),
we have $ r^2e^{rt}$ $-$ 2$re^{rt}$ $-$ 2$e^{rt}$ = 0 ,
$ e^{rt}$$(r^2 - 2r -2) = 0$
since $ e^{rt}$ is not zero
so $(r^2 - 2r -2) = 0$
we can get r = $\frac{2 \pm \sqrt{4 +8}}{2}$
simplify it we get  r = $\frac{2 \pm 2\sqrt{3}}{2}$
Then r = $1+ \sqrt{3}$ r = $1- \sqrt{3}$
Then two roots of equation (1) is  $e^{(1+ \sqrt{3})t}$ and $e^{(1- \sqrt{3})t}$
Therefore, the general solution is  y =$c_1$ $e^{(1+ \sqrt{3})t}$ + $c_2$ $e^{(1- \sqrt{3})t}$